Probiotics in feedlot cattle: implications for reducing liver abscess pathogens - Moe, Maggie Catherine Taylor (My University, 2025)
Liver abscesses are a significant health and economic issue in feedlot cattle, predominantly caused by Fusobacterium necrophorum, Trueperella pyogenes, and Salmonella enterica. These abscesses commonly result from ruminal acidosis or rumenitis associated with high-grain diets. While liver abscesses have traditionally been controlled with in-feed antimicrobials like tylosin and chlortetracycline, increasing concern over antimicrobial resistance drives the need for alternative therapies. This study aimed to investigate the potential of lactic acid bacteria (LAB) isolated from liver-abscess-free cattle as natural inhibitors of liver abscess-causing pathogens. Between 2 beef processing plants, ruminal content samples from 56 cattle were collected originating from 28 feedlots. From the samples collected, 560 LAB isolates were obtained, and broth cultures were separated into two cell-free aliquots: one with neutralized pH and the other remaining unaltered. Isolates were then screened for antimicrobial activity against the target liver abscess pathogens using agar-well diffusion assays. Results indicated that non-pH-adjusted LAB supernatants exhibited zones of inhibition for all three pathogens, with F. necrophorum showing the greatest inhibition and highest isolate sensitivity. However, pH-adjusted LAB supernatants displayed no antimicrobial activity, suggesting pH plays a significant role in the inhibitory effects observed. In total, 14 LAB isolates exhibited broad-spectrum inhibition across all pathogens, although repeated trials showed variability between experiments, highlighting the potential influence of LAB supernatant composition and culture conditions. Our findings suggest that ruminal LAB may exhibit innate antimicrobial effects against liver abscess pathogens, with Lactobacillus species showing potential for use in probiotics products for cattle on high-grain diets. Further research is needed to characterize these LAB isolates, assess their consistency and efficacy, and determine suitability as direct-fed microbial species for livestock production. This study highlights the potential of probiotics as viable substitutes to traditional antimicrobials for managing liver abscesses in feedlot cattle.
Keywords: Probiotics; Lactobacillus; Liver abscess; Fusobacterium necrophorum